(untitled) (Journal of Academic Research, 2024)
The linear absorption coefficient of beta particles in unsaturated polyester resin is an essential factor in radiation protection and medical imaging. This research aims at determining the impact of adding two forms of calcium carbonate, namely, pure calcium carbonate and eggshells on the linear absorption coefficient of beta particles in unsaturated polyester resin. Calcium carbonate and eggshells were selected as fillers since they have the possibility to enhance the radiation shielding capability of the resin. It is also revealed that the incorporation of both calcium carbonate and eggshells can enhance the linear absorption coefficient of beta particles in the unsaturated polyester resin for radiation protection. Further, the incorporation of natural additives such as eggshells is a better option as compared to synthetic fillers. As a result of this study it has been established that the adding of calcium carbonate and eggshells does affect the linear absorption coefficient of beta particles in unsaturated polyester resin. These results have significant implications for the fabrication of materials with desired radiation shielding characteristics and therefore, future work in this field should be continued to elucidate the underlying phenomena and to enhance the effectiveness of these composites.